Organized Crime and Criminal Offenses Against the Environment - Banović, Božidar; Ilić, Aleksandra (Glasnik Advokatske komore Vojvodine, 2026)
Standards for the protection and improvement of the environment, proclaimed by numerous political and guaranteed by legal documents at the international, national, and local levels, are in obvious and deep discord with the real situation. The environment is daily and continuously endangered and damaged by numerous and varied individual and collective activities, by natural persons as well as legal entities, business subjects, and even states themselves. Many of these activities have, over time, been prohibited and sanctioned by various types of regulations, while some, due to their frequency, prevalence, and severity of consequences, have been recognized as exceptionally socially dangerous and sanctioned by criminal legislation, thus receiving the name "environmental criminal offenses" or "environmental crime" in literature.Environmental crime is a very complex phenomenon that encompasses a wide spectrum of illegal activities and harmful consequences, which is one reason why, among others, there is no universally accepted definition for it. The consequences of environmental crime are numerous and diverse, such as increased pollution levels, degradation of natural habitats, reduction of biodiversity, disruption of ecological balance, increased risk of diseases, irreversible climate changes, contamination of the food chain, reduction in life expectancy, and even fatal outcomes. Besides the direct and indirect harmful consequences for the environment and human health, certain forms of environmental crime are aimed at acquiring profit for individuals, groups, or business entities (companies, corporations) through the exploitation, damage, trade, or theft of natural resources, or through the illegal trade and disposal of hazardous waste and other pollutants, as well as the smuggling of ozone-depleting substances. Advancements in technology, the development of new industrial plants, and the ever-increasing demand for natural resources have created fertile ground for the abuse of the environment for the sake of profit.Furthermore, modern forms of environmental criminal offenses, as a rule, have a transnational character. Although long viewed as an isolated problem, primarily of a local nature, environmental crime today represents one of the most serious and profitable threats to global security and the economy. The United Nations has highlighted environmental crime as a key factor exacerbating the so-called "triple planetary crisis" – climate change, biodiversity loss, and pollution. It is precisely the profitability and transnational character of environmental criminal offenses on the one hand, and the shortcomings of normative solutions and weaknesses in their application on the other, that have contributed to organized criminal groups and networks perceiving environmental crimes as an opportunity for high profit at a relatively low risk, allowing them to finance other illegal activities and expand their influence.In the scientific and professional public today, there is almost no dilemma that environmental crime is another form of transnational organized crime. According to estimates from relevant international organizations and agencies, environmental crime is designated as the fourth most lucrative criminal activity in the world, immediately after human, drug, and arms trafficking, generating up to 300 billion dollars in illicit profits annually. Despite official statistics not showing this, it is estimated that environmental crime is growing at an annual rate of 5%-7%, which makes it grow faster than other forms of organized criminal activity. While traditional forms of organized criminal activity are strongly in focus for both the international and national public, and thus under significant pressure from law enforcement agencies, the effective suppression of environmental criminal offenses is still not a priority in many countries today.Organized criminal groups and networks have recognized the potential for diversifying their criminal portfolios into environmental crime, using already established logistical routes, corrupt mechanisms, and money laundering methods. In this way, a mechanism of convergence is established between traditional forms of organized criminal activity and environmental crime, which manifests through the sharing of infrastructure (routes, warehouses, intermediaries), financial channels, corrupt networks, and violent security mechanisms, but also through normative gaps and weak oversight capacities.The introductory part of this paper provides conceptual definitions of environmental and organized crime, and then we will focus on key areas such as illegal logging and timber trade, trafficking in protected plant and animal species, illegal, unreported, and unregulated (IUU) fishing, illicit waste shipments, including electronic and medical hazardous waste, and illegal exploitation of mineral resources. In addition, the operational methodology of criminal networks will be examined, with special emphasis on corruption and money laundering as key factors contributing to convergence, as well as on the role of corporations and state bodies in these mechanisms. The paper will also present selected case studies from reports of relevant international organizations to illustrate the key characteristics of contemporary organized environmental crime and its sectoral and regional specificities. At the end of the paper, a brief critical review of the dynamics and state of environmental crime in Serbia will be provided
Keywords: environmental crime; organized crime; criminal networks; convergence of organized and environmental crime; corruption; money laundering